Developmental control of the DNA replication and transcription programs - Nordman, Jared; Li, Sharon; Eng, Thomas; MacAlpine, David; Orr-Weaver, Terry L. (Genome Research, 2011)
Polyploid or polytene cells, which have more than 2C DNA content, are widespread throughout nature and present in most differentiated Drosophila tissues. These cells also can display differential replication, that is, genomic regions of increased or decreased DNA copy number relative to overall genomic ploidy. How frequently differential replication is used as a developmental strategy remains unclear. Here, we use genome-wide array-based comparative genomic hybridization (aCGH) to profile differential DNA replication in isolated and purified larval fat body and midgut tissues of Drosophila, and we compare them with recent aCGH profiles of the larval salivary gland. We identify sites of euchromatic underreplication that are common to all three tissues and others that are tissue specific. We demonstrate that both common and tissue-specific underreplicated sites are dependent on the Suppressor of Underreplication protein, SUUR. mRNA-seq profiling shows that whereas underreplicated regions are generally transcriptionally silent in the larval midgut and salivary gland, transcriptional silencing and underreplication have been uncoupled in the larval fat body. In addition to revealing the prevalence of differential replication, our results show that transcriptional silencing and underreplication can be mechanistically uncoupled.